Sky juice - Sky Juice; Jig Production; Sony Music Entertainment (Malaysia). (Ampang, Selangor : Jig Production, 1997)
Contains eleven rock tracks.
CD 1 : Millenium 2...Who? / (5:40) -- Season Change Your Mind / (5:51) -- Free Trance / (3:51) -- Peace / (5:28) -- Ectasy -- Never Die -- Cry -- City Of Joy -- Secret -- Ectasy (tol free version).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English